2021
DOI: 10.34067/kid.0007322020
|View full text |Cite
|
Sign up to set email alerts
|

AKI in Hospitalized Patients with COVID-19 and Seasonal Influenza: A Comparative Analysis

Abstract: Background: Coronavirus disease 2019 (COVID-19) is often compared to seasonal influenza and the two diseases share similarities including the risk of systemic manifestations such as acute kidney injury (AKI). The aim of this study was to perform a comparative analysis of the prevalence, risk factors, and outcomes of AKI in hospitalized patients with COVID-19 and influenza. Methods: Retrospective cohort study of hospitalized patients with COVID-19 (n=325) or seasonal influenza (n=433). AKI was defined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
0
14
1
Order By: Relevance
“…Bhasin et al found a similar incidence of AKI in both groups (33%) in agreement with our results. In their study, however, COVID-19 was an independent risk factor for severe AKI compared to influenza, which was not the case in our study, and this may be due to the fact that the COVID-19 cohort and Influenza cohort had significant population differences which were not a covariate in their model [60].…”
Section: Discussioncontrasting
confidence: 91%
“…Bhasin et al found a similar incidence of AKI in both groups (33%) in agreement with our results. In their study, however, COVID-19 was an independent risk factor for severe AKI compared to influenza, which was not the case in our study, and this may be due to the fact that the COVID-19 cohort and Influenza cohort had significant population differences which were not a covariate in their model [60].…”
Section: Discussioncontrasting
confidence: 91%
“…However, in a prospective pilot study of 30 mechanically ventilated patients (15 with COVID-19 and 15 with ARDS due to other causes), the COVID-19 patients had decreased renal blood flow despite similar ventilatory management [92]. Similarly, in an analysis of over 750 patients hospitalized with influenza or COVID-19, the risk of stage 3 AKI was higher in the COVID-19 cohort than the influenza group, and mechanical ventilation was associated with an increased risk of AKI in the COVID-19 group but not the influenza cohort [93].…”
Section: Indirect Contributors To Covid-19-associated Akimentioning
confidence: 92%
“…In either pathway, the inflammatory and immunological response is a crucial key player in the pathophysiological process [ 3 , 4 ]. AKI due to COVID-19 compared to other forms of AKI appears to manifest in a worse phenotype of AKI in terms of incidence, severity, and electrolyte derangements [ 5 ].…”
Section: Introductionmentioning
confidence: 99%